Moderating effect of religious orientation on general Takaful product pricing and muslim customers purchasing behaviour - Ku Amir, Ku Daud (School of Business Innovation and Technopreneurship, Universiti Malaysia Perlis (UniMAP), 2021)
Link to publisher's homepage at https://ijbt.unimap.edu.my